Lexical relations in Ilokano for an Ilokano lexical database - Clausen, Josie P. (2006)
Approximately 60 kinds of lexical relations have been recognized in languages of the world (Grimes&Grimes, 1993). In this paper, I present evidence for a wide range of lexical relations in the Ilokano language. Grimes explains the meaning of lexical relations in terms of the way two words are related but differ in meaning, giving examples such as write and writer, row and rower. I will exemplify some of the types of lexical relations attested in Ilokano: 1) Verbs with an incorporated nominal, e.g. ag-diram'os' to wash one's face' where the implied noun is face'; aginnaw 'wash dishes', implied noun, 'dishes'. There is no word for face' in agdiram'os, nor word for 'dishes' in aginnaw. 2) Derived nouns expressing an agentive relation, e.g.from the verb agsugal 'to gamble' the derived noun is mannugal 'gambler', agsurat 'to write', mannurat'writer'. 3) Reduplication of a noun describing a condition of that noun, e.g. saka foot', saka-saka' barefoot'; ima'hand', irna-irna 'empty-handed'.4) Derived verbs denoting animal vocalization, e.g. aso 'dog', agtaol (phonation)'to bark', ul'ul'ol (onomatopoeia); 5) Derived verbs denoting a quantum, e.g. sangalilig a sua 'one section of a pomelo'; 6) Complements, e.g. biag ken patay 'life and death'; 7) Derived verbs denoting junction, e.g. karayan 'river', agayos 'to flow', sabong 'flower', agukrad 'to bloom'. I will then show how these derivations are handled in the Ilokano Lexical Database where they are listed making use of the band format.
Includes bibliographical references (page 60).